Hitting the Target but Missing the Mark: Unintended Environmental Consequences of the Paris Climate Agreement - Kiesecker, Joseph; Baruch-Mordo, Sharon; Kennedy, Christina M.; Oakleaf, James R.; Baccini, Alessandro; Griscom, Bronson W. (Frontiers in Environmental Science, 2019)
Meeting climate mitigation and sustainable development goals requires rapid increases in both renewable energy development and carbon storage in ecosystems. If sited with the sole goal of maximizing production, renewable energy may negatively impact biodiversity and carbon storage. Here, we evaluated the potential unintended environmental consequences of this type of business-as-usual development scenario. We spatially allocated land-based, utility-scaled wind and solar energy needed to achieve emission reduction goals from nationally determined contributions under the Paris Climate Agreement. Siting was conducted at 1-km resolution and followed a scenario where on-shore wind, concentrated solar power, and photovoltaic solar renewable energy developments were located where wind and solar resources were highest. Once sited, we evaluated the potential losses of natural lands, Key Biodiversity Areas (KBAs), threatened and endangered species, and carbon emissions. Over 11 million ha of natural lands can be lost (>1/4 in KBAs), releasing almost 415 million tons of carbon storage, which equals 8.6% of overall Paris Agreement emission reduction goals. Globally we found that the ranges of 1,574 threatened and endanger species could be impacted, with the highest numbers in the tropical countries of Indonesia (282), Malaysia (273) and Thailand (253). Avoiding land-based emissions through improved renewable energy siting can reduce these losses, potentially saving $47.5-$155.9 billion USD based on social carbon costs. Consideration of these impacts will help reduce investor risk to facilitate a timely transition to a low-carbon economy.